KRITIK MATAN (Sebuah Upaya Menjaga dan Meneropong Orisinalitas Hadîts) - Arif Wahyudi (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2009)
Matan critic is a critic that emphasizes to matan that comes fromneutral concept or suspicion to the validity of Hadîts from matanperspective. Many controversy of matan critic, such as when thisproblem is discussed, as soon as it will appear a blasphemy thatmeans it doubts the prophet’s utterance. Although matan critichas been done since the prophet’s friends era by comparingmatan of Hadîts with al-Qur’ân or the other Hadîts. They doubtedabout it even they refused a Hadîts that was considered ascontradiction of al-Qur’ân and the other Hadîts told by morecapable people. The ulama then covered this matan critic byusing the certain theories discussed in the study of Hadîtsdirâyah. On the other hand, many people said that matan critic isnot perfect and it needs to be functioned well.